National Regulations and Local Rules - A Hybrid Regulatory Model of Intelligent Connected Vehicles in China - Liu, Huichun (Advances in Social Sciences Research Journal, 2021)
This paper investigates the laws and regulations of China on the intelligent connected vehicles (ICV). After analyzing the current Chinese laws that are related to the ICVs, this paper makes a list of challenges that the current legal framework needs to face if (1) the ICV-related laws are not revised or new laws are not passed, and (2) there are no regulations or rules made to govern the legal issues of the ICVs. Then this paper starts to focus on the research into the national regulations and local government rules. In this part, literature review of the regulations of the central government and the rules of the local government is completed to investigate how this hybrid model works for the development of ICV industry in China. Detailed analysis of text of provisions is provided. The results indicate that the interaction and interconnection of the regulations at the national level and local government level form an underlying framework for the Chinese ICV industry by providing guidance, policies, and implementation rules.